The Thing about Religion : An Introduction to the Material Study of Religions - Morgan, David, 1957- (Book collections on Project MUSE., 2021)
"Common views of religion typically focus on the beliefs and meanings derived from revealed scriptures, ideas, and doctrines. David Morgan has led the way in radically broadening that framework to encompass the understanding that religions are fundamentally embodied, material forms of practice. This concise primer shows readers how to study what has come to be termed 'material religion' the ways religious meaning is enacted in the material world"--